O uso de membrana de Látex natural como cobertura e auxílio da fusão intervertebral lombar - Oliveira, Fabricio Arias Farina de (2010)
Artrhodesis posterolateral is one of the most common surgeries carried in the lumbar vertebra. It is a well recognized surgical method for treatment of some vertebral pathology including spondylolisthesis, scoliosis, kyphosis, vertebral degenerative illnesses and tumors. The success of the intertransverse fusion consists on the formation of a new bone matrix contiguous with the host bone. This bone matrix mineralizes and remodels, becoming mature with rigidity enough to support physiological loads without injury. To stimulate the bone formation, several procedures have been adopted. In this work we evaluate the influence of the natural latex membrane used as an occlusive membrane in addition to autogenous iliac crest bone graft in the lumbar intertransverse fusion process. Latex is a biocompatible material, capable to accelerate angiogenesis and is an efficient occlusive membrane for guided bone regeneration procedures. Eight male New Zealand White rabbits underwent posterolateral intertransverse process lumbar spinal fusion in the L4 and L5 vertebrae using iliac crest autograft. One of the sides was covered with natural latex membrane (treated side) and the other was kept only with graft (control side). The rabbits had been euthanized eight weeks pos surgery and the influence of the latex membrane was evaluated through manual palpation, qualitative histology, histomorphometry, radiography (plain radiograph and CT scan). The macroscopic analysis demonstrated fusion in six sides protected with membrane and five without the membrane and higher consistency of the osseous callus in the side treated with the membrane. The radiographic analysis demonstrated higher radiopacity area on the treated side in five of the eight rabbits. In only one of them the control side showed greater radiopacity, demonstrating the positive contribution of the latex membrane in the process of intertransverse fusion. The bone volume in the arthrodesis region assessed by Computerized Tomography showed that 5 of 8 rabbits (62.5%) presented greater bone volume in the treated side, 2(25%) presented the same volume and 1(12.5%) the volume of control side was greater than treated side, considering an error of 5% in the measurement process. The global results showed difference of means statically significant at p<0.1 level by ANOVA and Tukey test. The histomorphometric results were similar to bone volume CT measurements.